2020
DOI: 10.1002/jctb.6390
|View full text |Cite
|
Sign up to set email alerts
|

Comparative characterization and functional genomic analysis of two Comamonas sp. strains for biodegradation of quinoline

Abstract: BACKGROUND Quinoline is an ubiquitous pollutant widely spread in the environment, which can be eliminated efficiently by microbial degradation. In this study, two quinoline‐degrading Comamonas sp. strains Z1 and Z3 were isolated from activated sludge, and the degradation characteristics and genome annotation were investigated in detail. RESULTS Strain Z1 exhibited a superior capacity for quinoline degradation, which could completely degrade 50–300 mg L−1 quinoline within 8–24 h, whereas strain Z3 required 14–3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
(91 reference statements)
0
2
0
Order By: Relevance
“…Our data demonstrated that members of the Burkholderiaceae and Comamonadaceae, including Comamonas , Variovorax , and Methylibium , are highly abundant in samples that showed evidence of ametoctradin degradation. These species have been well studied and are commonly associated with xenobiotic degradation ( Vallaeys et al, 1998 ; Nakatsu et al, 2006 ; Satola et al, 2012 ; Chen et al, 2016a , b ; Öztürk et al, 2020 ; Zhang et al, 2020 ). In the packed-bed reactor, Comamonas spp.…”
Section: Discussionmentioning
confidence: 99%
“…Our data demonstrated that members of the Burkholderiaceae and Comamonadaceae, including Comamonas , Variovorax , and Methylibium , are highly abundant in samples that showed evidence of ametoctradin degradation. These species have been well studied and are commonly associated with xenobiotic degradation ( Vallaeys et al, 1998 ; Nakatsu et al, 2006 ; Satola et al, 2012 ; Chen et al, 2016a , b ; Öztürk et al, 2020 ; Zhang et al, 2020 ). In the packed-bed reactor, Comamonas spp.…”
Section: Discussionmentioning
confidence: 99%
“…JW. 30,31 According to the KEGG annotation, a total of 2169 genes were classified into 41 functional categories, mainly functioning in global and overview maps, amino acid metabolism, carbohydrate metabolism, and energy metabolism (Fig. 4(c)).…”
Section: Genes Related To Pah Degradation By Acidovorax Sp Jg5mentioning
confidence: 99%